Aminoglycoside-induced mutation suppression (stop codon readthrough) as a therapeutic strategy for Duchenne muscular dystrophy - Vinod Malik; Louise R. Rodino‐Klapac; Laurence Viollet; Jerry R. Mendell (2010)
Duchenne muscular dystrophy (DMD) is the most common, lethal, X-linked genetic disease, affecting 1 in 3500 newborn males. It is caused by mutations in the DMD gene. Owing to the large size of the gene, the mutation rate in both germline and somatic cells is very high. Nearly 13-15% of DMD cases are caused by nonsense mutations leading to premature termination codons in the reading frame that results in truncated dystrophin protein. Currently there is no cure for DMD. The only available treatment is the use of glucocorticoids that have modest beneficial effects accompanied by significant side effects. Different therapeutic strategies have been developed ranging from gene therapy to exon skipping and nonsense mutation suppression to produce the full-length protein. These strategies have shown promise in the mdx mouse model of muscular dystrophy where they have been reported to ameliorate the dystrophic phenotype and correct the physiological defects in the membrane. Each of these molecular approaches are being investigated in clinical trials. Here we review nonsense mutation suppression by aminoglycosides as a therapeutic strategy to treat DMD with special emphasis on gentamicin-induced readthrough of disease-causing premature termination codons.